Contemporary Literary Sports Journalism - McGowan, Lee. author. (orcid)0000-0003-1255-453X Link aut Link
XIV, 198 p. 2 illus.
Keywords: This book offers new perspectives on the practices and production of contemporary literary sports journalism, considering the form within theoretical frameworks related to critical studies in sports media, sports journalism, creative writing, and literary studies. The book’s approach to innovative literary sports journalism and its scholarship offers a unique academic interrogation of contemporary and emergent practices in the field, exploring the intersections between examples of sports journalism and literature, and those works in related forms of literary journalism. It also builds on the work of its own experienced authorial team – established scholars in related academic research with extensive sports-related research networks and professional practitioners in sports writing, journalism, and related forms. Lee McGowan is a senior lecturer at the University of the Sunshine Coast. Kasey Symons is a Lecturer of Communication – Sports Media at Deakin University. Paddy Hoey is a senior lecturer in Media, Culture and Communication with International Relations and Politics at Liverpool John Moores University. Elizabeth Ellison is Dean of Research for the Creative Academic Unit at the University of South Australia.